THE FACTORS AFFECTING THE TREASURERS’ PERFORMANCE REGIONAL WORK UNIT IN SAMOSIR REGENCY AND MOTIVATION AS MODERATING VARIABLE - Amriady, Krismanto Manik (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to examine and to analyze the influence of Education, Training, and Clarity of Role on the treasurers’ performance at SKPD (Regional Work Unit) in Samosir Regency and motivation as moderating variable. The type of this research was causality research. The population was the treasurers of revenue, treasurers of expenditure, assistant treasurers of revenue, and assistant treasurers of expenditure in all SKPDs in Samosir Regency. There are 81 respondents from 38 SKPDs.  This research used census method. This research used primary data of the questionnaire results given to the respondents. The data were analyzed by using multiple linear regression analysis and residual test. The results of the research showed that Education, Training and Clarity of Role simultaneously and partially had significant influence on treasures’ performance at the SKPDs in Samosir Regency. Motivation can moderate the correlation of Education, Training and Clarity of Role with treasures’ performance at the SKPDs in Samosir Regency.